EFL pre-service teachers’ challenges in teaching English to young learners during Kampus Mengajar program in rural areas - Wahidah Nurul Hikmah; Irma Windy Astuti (Universitas Muhammadiyah Malang, 2025)
In recent time, several studies have discussed the challenges frequently faced by pre-service EFL teachers (PSEFLTs) while conducting their teaching practice in rural areas. However, studies about the challenges faced by PSEFLTs in Indonesian primary education context, especially under the Kampus Mengajar program is still lacking. The main objective of this study is to describe the challenges experienced by PSEFLTs during their teaching practicum at the primary-levels under the Kampus Mengajar program which took place in schools with limited facilities in remote areas. This study used qualitative research design, and involved two PSEFLTs from a private Islamic University in Yogyakarta participating in the Kampus Mengajar program for one semester. To gather the data, this study employed interviews as its primary data collection technique, complemented by documents as the secondary means. The study finding identified four challenges relating to three major themes, namely: 1). Pre-service teachers’ pedagogical competencies and 2). The development of learning materials and media, and 3) an emergent finding which revealed the institutional-related challenges. In reference to the findings, this study subsequently suggests the importance of providing additional and more contextualized training for pre-service teachers prior to their teaching practicum to orient and prepare them in dealing with the dynamic of teaching and learning in remote schools with limited facilities to perform more effectively and contribute meaningfully to the program